Temperature measurements by means of the electrical impedance of piezoceramics - Ilg, Jürgen; Rupitsch, Stefan; Lerch, Reinhard (Institute of Electrical and Electronics Engineers, 2012)
This contribution deals with the temperature dependence of the electrical impedance of piezoceramic transducers. The behavior under thermal loads is investigated for bulk ceramics and composite structures where the piezoceramics are integrated into passive materials. According to this identified dependencies, temperature measurements by means of the piezoceramics impedance is realized using a polynomial fitting method. The accuracy of the measurements is investigated for different temperature profiles. The presented method can be utilized for additionally measuring temperature in devices with integrated piezoceramic transducers, especially in health monitoring applications.